2010
DOI: 10.1371/journal.pmed.1000283
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Phenotypic and Genotypic G6PD Deficiency on Risk of Plasmodium vivax Infection: A Case-Control Study amongst Afghan Refugees in Pakistan

Abstract: Analyses of a case-control study among Afghan refugees in Pakistan find that a G6PD (glucose-6-phosphate dehydrogenase) “Mediterranean” type deficiency confers substantial protection against Plasmodium vivax malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 30 publications
4
94
1
Order By: Relevance
“…Recently, evidence has suggested that G6PD deficiency caused by the Mahidol mutation in Southeast Asians provides parasite resistance to infection by P. vivax, but not to that by P. falciparum. Further, G6PD deficiency Med in Pakistan has been shown to provide protection from P. vivax malaria (Leslie et al, 2010).…”
Section: G6pd Deficiencymentioning
confidence: 99%
“…Recently, evidence has suggested that G6PD deficiency caused by the Mahidol mutation in Southeast Asians provides parasite resistance to infection by P. vivax, but not to that by P. falciparum. Further, G6PD deficiency Med in Pakistan has been shown to provide protection from P. vivax malaria (Leslie et al, 2010).…”
Section: G6pd Deficiencymentioning
confidence: 99%
“…G6PD is an important issue related to P. vivax malaria. A Mediterranean type of G6PD deficiency significantly protects against P. vivax infection among Afghan refugees in Pakistan (32). A similar report is also available for the G6PD Mahidol variant from Southeast Asia (33).…”
Section: Discussionmentioning
confidence: 75%
“…FY*B/FY*X and FY*A/FY*X genotypes are associated with low parasite density, which may favorably impact hemoglobin levels (69). Observational studies have shown protection against P. vivax infections conferred by a RBC enzyme (glucose-6-phosphate dehydrogenase) deficiency (70)(71)(72) and an erythrocyte membrane disorder (Southeast Asian ovalocytosis) by a mechanism that is independent of the Duffy antigen (73). On the other hand, thalassemias, which are disorders of globin synthesis, appear to increase the susceptibility to vivax malaria in carrier populations from different geographic regions (74)(75)(76)(77).…”
Section: Overview Of the Major Determinants Of Vivax Anemiamentioning
confidence: 99%